2021
DOI: 10.1063/5.0071042
|View full text |Cite
|
Sign up to set email alerts
|

On the role of the energy loss function in the image force on a charge moving over supported graphene

Abstract: We use a dielectric response theory to describe electrodynamic forces on a charged particle moving parallel to a supported two-dimensional layer. Using a Kramers–Kronig relation, we show that the image force on the particle can be expressed in terms of the energy loss function of the target materials. This enables us to analyze the stopping and the image forces on the particle on equal footing in the frequency–momentum domain encompassing all the energy loss channels in the target. Using the example of a graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“… 39 A carbon/LCO ohmic contact is formed, in this case the positive charge/ion inside the crystal forms a negative image charge at the carbon coating layer that in turn attracts the positrons, as predicted by Rivas et al. 40 In fact, Shi et al. 41 , 42 have shown that “positrons” are a highly sensitive probe at the coating/semiconductor quantum dots interface.…”
Section: Resultsmentioning
confidence: 82%
“… 39 A carbon/LCO ohmic contact is formed, in this case the positive charge/ion inside the crystal forms a negative image charge at the carbon coating layer that in turn attracts the positrons, as predicted by Rivas et al. 40 In fact, Shi et al. 41 , 42 have shown that “positrons” are a highly sensitive probe at the coating/semiconductor quantum dots interface.…”
Section: Resultsmentioning
confidence: 82%
“…While this assumption is necessary to validate the neglect of the magnetic fields due to the moving particle, a fully relativistic formulation of the problem showed that the magnetic field due to the induced current in a conducting sheet may only be neglected if one additionally assumes that , see Equation ( 6 ) in [ 17 ]. This inequality is automatically satisfied by assuming for a particle moving parallel to the sheet because of the resonance condition [ 28 , 29 ], but for the perpendicular trajectory in Figure 1 , a strong hybridization of the plasmon dispersion with the light line can affect the launching of plasmons with long wavelengths, even when . The proximity of the region , which was shown to give rise to a sizeable radiative energy loss in doped graphene in the THz-MIR frequency range [ 22 , 23 , 24 ], renders the issue of the nonrelativistic approximation rather nontrivial in the present context.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Even before we commit to the study of a particular conductivity model, we can make a number of theoretical developments assuming that the 2D sheet is isotropic, so that its conductivity depends on the norm and is also an arbitrary complex function of frequency that must satisfy certain general properties [ 22 , 28 ]. The quantity of primary interest in this section is the integral which is related to the expression for the induced potential in the -domain by as can be seen from our convention ( 2 ) for the Fourier transform.…”
Section: Theoretical Modelmentioning
confidence: 99%
See 2 more Smart Citations